Lipases microbianas: produção, propriedades e aplicações biotecnológicas - Messias, Josana Maria; Costa, Bruna Zucoloto da; Nascimento, Valeria Marta Gomes do [UNESP]; Giese, Ellen Cristine; Dekker, Robert F H; Barbosa, Aneli de Melo (Universidade Estadual de Londrina, 2011)
Lipases belong to the group of hydrolases that catalyze the hydrolysis of triacylglycerol lipids to free fatty acids and glycerol. They have significant potential biotechnological applications in catalyzing organic synthesis reactions in non-aqueous solvents using simplified procedures resulting in conversions of high yields. Lipase production has conventionally been performed by submerged fermentation; however, solid-state fermentation processes have been prominent when residues are used as substrates because they serve as low-cost nutrient sources. Microbial lipases can be used as additives in foods to modify and enhance organoleptic properties, as well as in detergents to hydrolyse fats in the treatment of oily effluents, and also have value for pharmaceutical, cosmetic, agrochemical, and oil chemical industries. More recently, they are used in transesterification reactions to convert plant seed oils into biodiesel. The objective of this work was to review the published literature on the production, properties and applications of microbial lipases, and its biotechnological role in producing biodiesel.

Lipases pertencem ao grupo das hidrolases que catalisam a conversão de triacilgliceróis a ácidos graxos livres e glicerol. Possuem significante potencial biotecnológico como catalisadores em reações de síntese orgânica em meio não aquoso utilizando processos simplificados com altos rendimentos. A produção de lipases tem sido realizada, usualmente, por processo fermentativo submerso; entretanto, o processo em fase sólida também tem se mostrado promissor, quando são utilizados resíduos como fontes de substrato que são nutrientes de baixo custo. As lipases microbianas podem ser utilizadas como aditivos em alimentos para modificar e realçar as propriedades organolépticas, como também em detergentes para hidrolisar gorduras, no tratamento de efluentes oleosos, e ainda, nas indústrias farmacêuticas, de cosméticos, agroquímicas e oleoquímicas. Recentemente, as lipases têm sido utilizadas em reações de transesterificação para converter óleos em biodiesel. O objetivo deste trabalho foi revisar a literatura publicada sobre a produção, propriedades e aplicações das lipases microbianas e o seu papel biotecnológico na produção do biodiesel.
Microbial lipases: production, properties and biotechnological applications
Keywords: Enzymes; Microbial enzymes; Enzyme applications; Biodiesel; Enzimas; Enzimas microbianas; Aplicações de enzimas; Biodiesel